High robustness energy- and area-efficient dynamic-voltage-scaling 4-phase 4-rail asynchronous-logic Network-on-Chip (ANoC) - Ho, Weng-Geng (2016)
We propose an 18-bit 5-interface asynchronouslogic Network-on-Chip (ANoC) router based on the quasi-delayinsensitive (QDI) realization approach for high secured cryptography applications. There are four key features of the proposed ANoC router. First, it embodies the novel high-speed low-power Sense-Amplifier Half Buffer 4-rail cells. Second, it is designed based on QDI protocol, and hence is highly robust against process-voltage-temperature (PVT) variations. Third, it is functional for full dynamic voltage scaling from nominal (VDD=1.2V) to sub-threshold (VDD=0.3V) regions, and is potentially excellent for low power management applications. Fourth, it embodies a distributed-based XY routing algorithm to utilize a 4-bit header of flow control unit (flit) for routing up to 4×4 cluster, hence minimizing the routing overhead. We realize the proposed ANoC router (@65nm CMOS), and benchmark it against the reported ANoC router embodying the conventional Weak-Conditioned Half-Buffer (WCHB) QDI realization approach. Both our proposed and reported designs feature the high operation robustness, but our design is 41% more energy efficient, and 21% more area-efficient than the reported counterpart. The prototype of ANoC router occupies only 0.105 mm2 and can operate down to 0.3V. At VDD=0.3V, it dissipates 44 fJ per bit and operate 105 ns per flit.